(untitled) (Journal of Geography and Environmental Management, 2017)
At present, in Kazakhstan a number of large mining companies successfully introduce modern mining and geo-information technologies that significantly improve the efficiency of exploration and extraction of mineral raw materials. Such companies include Kazakhmys Corporation, Zhayrem’s QUM, Belogorsk QUM, Kazzinc LLP, Zhezkent QUM and others. These enterprises use modern mining and geo-information technologies of world famous companies («Datamine», «GEMCOM», «Vulcan», «Micromine», «Surpac», etc.) and with its help successfully perform three-dimensional modeling of complex geological objects, Reserves of deposits, optimize and design quarries and underground mines. Also, this article demonstrates the possibilities of using geoinformation (GIS) technologies in the design and creation of automated cartographic information systems for solving a wide range of engineering and scientific problems of mining – mining, environmental and socio-economic problems arising from the development of subsoil. The main purpose of this article is to create a 3D model of the field using GIS technologies, to improve the efficiency and safety of mining operations.